Handcycling with concurrent lower body low-frequency electromyostimulation increases acute oxygen uptake in elite wheelchair basketball players: An acute crossover trial - Micke, F.; Rappelt, L.; Held, S.; Wiedenmann, T.; Deutsch, J. P.; Kleinöder, H.; Donath, L. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Acute increases in oxygen uptake (VO2) during exercise are crucial for aerobic training adaptations and depend on the amount of muscle involved. VO2 capacity is limited during wheelchair handcycling due to restricted muscle involvement of the impaired lower body muscles. Handcycling with concurrent complementary low-frequency electromyostimulation (LF-EMS), applied to major lower limb muscles might lead to relevantly increased passive muscle involvement with higher oxygen uptake in elite wheelchair basketball (WCB) athletes.